'Sharp Ears to Hear a Thunderclap'? The rise of mediation in the international dispute prevention and settlement system of the belt and road initiative. Issue 1 (2nd January 2021) - de la Rasilla, Ignacio
ABSTRACT: The Convention on International Settlement Agreements Resulting from Mediation is one of the newest contributing factors to a virtuous circle upholding the foreseeable rise of mediation in cross-border business and investment disputes. This article analyses how the on-going institutionalization of the international dispute prevention and settlement system of the Belt and Road Initiative (BRI) is both being informed by, and is further contributing to, the global rise of mediation at a time when the international adjudicative system is in turmoil. The BRI is bound to generate a large number of complex international disputes ranging from international trade to investment and commercial disputes. This, in turn, has spurred two notable developments: 1) Chinese and regional arbitral institutions, legal regimes and investment treaty networks are currently adapting to better cater for the growing demand for commercial and investment arbitration in the context of the BRI. 2) The China International Commercial Court, which innovatively integrates 'litigation, arbitration and mediation' in its new 'one-stop' diversified settlement system, and a series of legal and institutional initiatives, namely the new International Commercial Dispute Prevention and Settlement Organization, are, in turn, paving the way for a greater use of mediation in cross-border business and investment disputes in the context of the BRI. This article examines these developments in the light of China's broader relationship with international adjudication and elaborates on a number of arguments to help rationalising why mediation is gaining ground in the on-going institutionalization of the International Dispute Prevention and Settlement System of the BRI.